A monolithically integrated silicon modulator with a 10 Gb/s 5 Vpp or 5.6 Vpp driver in 0.25 μm SiGe:C BiCMOS - Goll, Bernhard; Thomson, David J.; Zimmermann, Lars; Porte, Henri; Gardes, Frederic Y.; Hu, Youfang; Knoll, Dieter; Lischke, Stefan; Tillack, Bernd; Reed, Graham T.; Zimmermann, Horst (Frontiers in Physics, 2014)
This paper presents as a novelty a fully monolithically integrated 10 Gb/s silicon modulator consisting of an electrical driver plus optical phase modulator in 0.25 μm SiGe:C BiCMOS technology on one chip, where instead of a SOI CMOS process (only MOS transistors) a SiGe BiCMOS process (MOS transistors and fast SiGe bipolar transistors) is implemented. The fastest bipolar transistors in the BiCMOS product line used have a transit frequency of ft ≈ 120 GHz and a collector-emitter breakdown voltage of BVCE0 = 2.2 V (IHP SG25H3). The main focus of this paper will be given to the electronic drivers, where two driver variants are implemented in the test chips. Circuit descriptions and simulations, which treat the influences of noise and bond wires, are presented. Measurements at separate test chips for the drivers show that the integrated driver variant one has a low power consumption in the range of 0.66 to 0.68 W but a high gain of S21 = 37 dB. From the large signal point of view this driver delivers an inverted as well as a non-inverted output data signal between 0 and 2.5 V (5 Vpp differential). Driver variant one is supplied with 2.5 V and with 3.5 V. Bit-error-ratio (BER) measurements resulted in a BER better than 10−12 for voltage differences of the input data stream down to 50 mVpp. Driver variant two, which is an adapted version of driver variant one, is supplied with 2.5 and 4.2 V, consumes 0.83 to 0.87 W, delivers a differential data signal with 5.6 Vpp at the output and has a gain of S21 = 40 dB. The chip of the fully integrated modulator occupies an area of 12.3 mm2 due to the photonic components. Measurements with a 240 mVpp electrical input data stream, 1.25 V input common-mode voltage and for an optical input wavelength of 1540 nm resulted in an extinction ratio of 3.3 dB for 1 mm long RF phase shifters in each modulator arm driven by driver variant one and a DC tuning voltage of 1.2 V. The extinction ratio was 8.4 dB at a DC tuning voltage of 7 V for a device with 2 mm long RF phase shifters in each arm and driver variant two.